Prognostic impact of circulating tumor cells detected with the microfluidic "universal CTC‐chip" for primary lung cancer. Issue 3 (28th January 2022) - Kanayama, Masatoshi; Kuwata, Taiji; Mori, Masataka; Nemoto, Yukiko; Nishizawa, Natsumasa; Oyama, Rintaro; Matsumiya, Hiroki; Taira, Akihiro; Shinohara, Shinji; Takenaka, Masaru; Yoneda, Kazue; Kuroda, Koji; et al.
Abstract: Detecting rare circulating tumor cells (CTCs) in the bloodstream is extremely challenging. We had previously developed a novel polymeric microfluidic device, "CTC‐chip, " for capturing CTCs and have shown high capture efficiency in lung cancer cell lines by conjugating Abs against epithelial cell adhesion molecules (EpCAM). This study aimed to optimize the EpCAM‐chip and clarify the prognostic impact of CTCs in lung cancer patients. Of 123 patients with pathologically proven lung cancer, both progression‐free survival ( P =  .037) and cancer‐specific survival ( P  = .0041) were predominantly poor when CTCs were detected before treatment. After classification into surgical and chemotherapy groups, progression‐free survival was worse in CTC‐positive patients in both groups (surgery, P  = .115; chemotherapy, P  = .012), indicating that the detection of baseline CTCs is a risk factor for recurrence and progression. Furthermore, we recovered captured CTCs using micromanipulators and undertook mutation analysis using PCR. Thus, the EpCAM‐chip is a highly sensitive system for detecting CTCs that contributes to the prediction of recurrence and progression and enables genetic analysis of captured CTCs, which could open new diagnostic, therapeutic, and prognostic options for lung cancer patients. Abstract : This study aimed to optimize the epithelial cell adhesion molecule (EpCAM)‐chip and clarify the prognostic impact of circulating tumor cells (CTCs) in lung cancer patients. The EpCAM‐chip is a highly sensitive system for detecting CTCs. The EpCAM‐chip contributes to the prediction of recurrence and progression and enables genetic analysis of captured CTCs, which could open new diagnostic, therapeutic, and prognostic options for lung cancer patients.